Gender and job satisfaction: A European analysis in the light of gender ideology - Coron, Clotilde (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
The gender-job satisfaction paradox, i.e., women reporting higher levels of job satisfaction while facing worse working conditions, has been hotly debated by scholars. This article studies the moderating role of national gender ideology in this paradox. In particular, the focus on Anglo-Saxon countries as well as the lack of attention towards the role of national gender ideology have received criticism. National gender ideology moderates the relationship between gender and job satisfaction: in more egalitarian countries, the gender gap of job satisfaction (to the detriment of women) is more important than in countries with more traditional gender ideologies. These results allow us to discuss expectation theory and the transitory nature of the gender-job satisfaction paradox.